Velocity of Chromosome Replication in Thymine-Requiring and Independent Strains of Bacillus subtilis - Ephrati-Elizur, Erela (1971)
Chromosomes in spores of a thymineless mutant of Bacillus subtilis strain 168 were shown to have a replication fork, unlike chromosomes in spores of the thy(+) strain which are in a complete form. As a consequence the number of replication forks in germinating cultures is higher in the thy(−) strain than in the thy(+) one. Chromosome replication time (C) in the thy(+) strain was found to be about 53 min for growth rates from 20 to 60 min. In the thy(−) strain, C was about 75 min at high growth rates and increased with decreasing growth rate when the thymine concentration was not limiting. With limiting thymine concentrations in the medium replication velocity decreased independently of growth rate.